Profile Of Physical Fitness Basketball Student Extracurricular - Rubiyatno Rubiyatno; Eka Supriatna; Rahmat Putra Perdana (UNIB Press, 2022)
The purpose of this study was to determine the level of physical fitness of students participating in basketball extracurricular training. This research is descriptive quantitative with survey methods. TKJI test and measurement (Indonesian physical fitness test) to determine the level of physical fitness in students. The research sample consisted of 20 male students in extracurricular basketball at Madrasah Tsanawiyah Negeri 1 Pontianak. The data obtained in the field are the results of TKJI aged 13-15 years, the data analysis uses descriptive percentages, then the data calculation is assisted using the Microsoft Excel software application. The results of the study were 13 students in the medium category with a percentage of 65% and the less category with a percentage of 35% as many as 7 students. The conclusion is that the level of physical fitness is in the moderate category, the results of this study prove that basketball extracurricular physical fitness is still relatively low.